Beyond the "Win-Win": Creating Shared Value Requires Ethical Frameworks. (February 2017) - de los Reyes, Gastón; Scholz, Markus; Smith, N. Craig
While Porter and Kramer's Creating Shared Value (CSV) works well as a management framework to address "win-win" business and society issues, it leaves managers ill-equipped to legitimately manage issues where they face the prospect of "win-lose" or "lose-win" social engagements. For legitimacy, managers need to bolster CSV with ethical frameworks—specifically, norm-taking and norm-making frameworks. Managers can be better positioned to create shared value through CSV+, a multi-part framework built around CSV and augmented by ethical frameworks.